EVALUASI KEBIJAKAN PEMBINAAN PRESTASI CABANG OLAHRAGA SQUASH PROVINSI RIAU - Rahmad Diyanto, - (2020)
The purpose of this study was to determine the policy evaluation of performance training in the Riau province's squash branch. The subjects of this study were athletes who had participated in the squash championship at the national level of the coach and organizer of the Indonesian squash union in Riau Province, totaling 6 people. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique in this study is in the field of the Miles and Huberman model, which is also referred to as the interactive data analysis technique where the data analysis is carried out interactively and continues continuously until it is complete, so that the data is saturated. The results of the study are as follows; 1) The role of infrastructure such as facilities and infrastructure is not optimal, 2) difficult access such as the field makes training or recruitment of athletes hampered, 3) Lack of superior HR trainers, 4) At least championships that are followed, 5) Limited funds owned for do try out and try in. Based on various problems that exist, the role of the Riau Province Sports Branch Management is needed in solving this achievement problem.